Student Characteristics and Motivation in Rural High Schools - Patricia L. Hardre; David W. Sullivan; H. Michael Crowson (Journal of Research in Rural Education, 2009)
This research tested a path model for how rural high school students' self-perceptions and environmental perceptions influence their course-related interest, school engagement, and ultimately, post-graduation intentions. Participants were 414 students in all four grades, in 10 rural, public high schools. Correlation and path analyses (in LISREL 8.58) were utilized to identify significant paths and test model fit. All paths in the final model were statistically significant and demonstrated good fit. Among environmental factors, teacher support predicted student interest in subject matter. Of personal characteristics, learning goals and perceived competence most strongly predicted interest and achievement, and content-related perceptions of instrumentality and value strongly predicted class effort as well as future intentions to finish high school and go on to postsecondary education. Overall, these rural students exhibited positive motivational profiles for learning, apart from achievement. However, the MANOVA analysis demonstrated significantly lower motivational profile for math than for all other subjects.